University-Industry Linkages as Determinant Of Students’ Entrepreneurial Orientation in Rivers State Public Universities - Ikpesu, Oghenerukevwe Christian (Advances in Social Sciences Research Journal, 2016)
Linkages are assuming unusual popularity as a platform for technology transfer, knowledge sharing and seeking support by universities from industry. Thus, the study examined university-industry linkages to determine its resultant implications to students’ entrepreneurial orientation in public universities in Rivers States. The population, therefore, consists of 160 academic administrators involve in designing policy frameworks and curriculum reforms that strengthens linkages with industry in their respective universities. Two independent measurement scales having four Likert points contained 13-item each measured the critical contributions of university-industry linkages and its implications to students’ entrepreneurial orientation (EO). The two sets of questionnaire computed with Cronbach Alpha provided 0.87, 0.78 reliability index. Data finally gathered from 150 respondents were analyzed using mean statistics and hypothesis tested with Pearson product moment correlation coefficient and Z-test at 0.05 level of significant showed + 0.376, Zrcal 0.561and Zrcrit value of 0.195. In conclusion, the results however affirmed subsisting relationship which significantly underscores the contributions and consequences of university-industry for developing students’ entrepreneurial orientation in public universities. Therefore Governments should strengthen the various linkages policy frameworks to encourage and drive the objectives of entrepreneurship education of producing students with high entrepreneurial contents that can fit well into self-employment and global labour market.